2014
DOI: 10.11604/pamj.2014.19.274.3604
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcome de Darier et Ferrand: propos de 38 cas

Abstract: Le dermatofibrosarcome protubérans de Darier et Ferrand est une tumeur cutanée rare. Le but de cette étude est de décrire les aspects épidémiologiques, cliniques, histologiques, thérapeutiques et évolutifs avec comparaison aux données de la littérature. Il s'agissait d'une étude rétrospective sur 10 ans à propos de 38 cas de dermatofibrosarcome de Darier et Ferrand pris en charge à l'Institut National d'Oncologie. Les données épidémiologiques, diagnostiques, thérapeutiques et évolutives ont été recueillies à p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…The two-year progression-free survival was 60%, and the two-year overall survival was 78% with 10 partial responses (67%), two stable diseases (13%) and three progressive diseases (20%). All of these studies confirmed the important anti-tumor effect of Imatinibin DFS harboring the t (17; 22) translocation [14][15][16][17].…”
Section: Discussionsupporting
confidence: 59%
“…The two-year progression-free survival was 60%, and the two-year overall survival was 78% with 10 partial responses (67%), two stable diseases (13%) and three progressive diseases (20%). All of these studies confirmed the important anti-tumor effect of Imatinibin DFS harboring the t (17; 22) translocation [14][15][16][17].…”
Section: Discussionsupporting
confidence: 59%
“…Darier-Ferrand dermatofibrosarcoma was first described by Darier and Ferrand in 1924, it appears at any age and generally affects young adults between the ages of 20 and 50. It is rarely metastatic but at high risk of local recurrence after tumor excision (El Kacemi et al, 2014). It is a rare tumor of the dermis of mesenchymal origin which accounts for 1 % of malignant soft tissue tumors and 0,1 % of all other malignant tumors (Sevim et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by high recurrence, slow growth, and low metastatic potential and occurs mainly in adults at any age, but mostly between their second and fifth decades of life (Al Barwani et al, 2016). The diagnosis is confirmed by histopathological examination and treatment involves surgery with wide margins of three to five centimeters (cm) to reduce the rate of recurrence (El Kacemi et al, 2014). Although several clinical cases of an unusual variant of DFS have been reported in the literature, localization on the palmar face of the hand is not common.…”
Section: Introductionmentioning
confidence: 99%
“…C'est la découverte de cette anomalie génétique présente dans 95% des cas qui permet actuellement d'envisager un diagnostic moléculaire et qui a permis également l'introduction de l'imatinib (Glivec®) dans le traitement [8]. Du point de vue thérapeutique, la chirurgie constitue la pierre du traitement [9,10]. Le DFS est réputé être une tumeur agressive localement avec un potentiel de récidive très élevé.…”
Section: Discussionunclassified
“…Le DFS est caractérisé par un index mitotique très bas, ce qui explique la faible réponse à la radiothérapie [7]. Cependant, certains auteurs ont rapporté un meilleur contrôle local par chirurgie large suivie de radiothérapie délivré à 50 ou 60 Gray selon qu'on soit en R0 ou R1, mais il s'agit de courtes séries ne permettant pas de prouver l'efficacité de ce schéma thérapeutique [9,10]. Pour la chimiothérapie, il n'existe pas de protocole claire ayant fait la preuve de son efficacité.…”
Section: Discussionunclassified